One week stenting after pediatric laparoscopic pyeloplasty; is it enough?. Issue 1 (February 2020) - Abdelwahab, M.; Abdelaziz, A.; Aboulela, W.; Shouman, A.M.; Ghoneima, W.; Shoukry, A.; Kassem, A.; Abdelhamid, M.; Abdelhakim, M.; ElGhoneimy, M.; Morsi, H.; Badawy, H.; et al.
Summary: Introduction: The use of ureteric stents for urinary diversion after pediatric dismembered pyeloplasty and its duration remain debatable. Classically, an indwelling Double J ureteric stent has to be left for 4–6 weeks. However, such a duration is not free of stent-related complications, in addition to the need to remove it under general anesthesia in the pediatric age group. Objectives: This study aims to evaluate the outcome of short-term stenting after laparoscopic pyeloplasty in pediatric sector. Methods: A prospective randomized study of 37 children (less than 16 years-old) with pelvi-ureteric junction obstruction (PUJO) were managed by laparoscopic pyeloplasty by the same surgeon in the period between April 2015 and September 2017. In group A (18 patients), the DJ was removed after 4 weeks under general anesthesia, while in group B (19 patients), the DJ was fixed to the urethral catheter by a stitch, and it was removed with the urethral catheter after one week in the outpatient office. All patients were followed regularly for symptomatic improvement. Urine culture and sensitivity was done 1 month postoperatively. Abdominal ultrasound was done at 3, 6, 12 months and annually thereafter, while renal isotope scanning was done after 6 months. Results: There were no significant differences between both groups regarding operative duration, postoperative leakage, hospital stay, early postoperative complications. Both groups improved after pyeloplasty with no significant differences regarding symptoms, follow-up ultrasound, and renal scanning. The incidence of irritative symptoms and need for anticholinergics after catheter removal as well as urinary tract infection after 1 month were significantly higher in group A ( P- value: 0.004 and 0.029, respectively) (Table). Discussion: To the authors knowledge, this is the first prospective controlled randomized study comparing short-term stenting with the classic 4 weeks stenting after laparoscopic pyeloplasty in the pediatric age group. In addition, the used technique of stenting not only allows stent removal on outpatient basis without anesthesia but also benefits from the pre-operative retrograde study so as not to miss any associated pathology in the ureter. Conclusion: Short-term ureteric stenting after laparoscopic pyeloplasty in pediatric age group is safe and not inferior to the standard 4-week stenting. It also avoids the stent-related complications. Summary Table Postoperative course and follow-up. Table 1   Group Group A Group B P -value PO complications No 16 (88.9%) 17 (89.5%) 1 Ileus 2 (11.1%) 1 (5.3%) Fever 0 (0%) 1 (5.3%) PO hospital stay (days) (mean ± SD) 2.50 ± 0.7 2.47 ± 0.7 0.916 Back to usual activity (days) (mean ± SD) 14.72 ± 1.41 14.32 ± 1.38 0.518 Follow-up (months) (mean ± SD) 21.56 ± 7.82 21.95 ± 7.94 0.893 Need to add anticholinergics Yes 11 (61.1%) 3 (15.8%) 0.004 No 7 (38.9%) 16 (84.2%) Urine culture after 1 month Clear 10 (55.6%) 17 (89.5%) 0.029 Infected 8 (44.4%) 2 (10.5%) Loin pain improved Yes 18 (100.0%) 19 (100.0%) – No 0 (0%) 0 (0%) Follow-up US after 3–6 months Improved 16 (88.9%) 17 (89.5%) 1 Stable 2 (11.1%) 2 (10.5%) Worsened 0 (0%) 0 (0%) Follow-up US after 12 months Improved 18 (100.0%) 19 (100.0%) – Stable 0 (0%) 0 (0%) Worsened 0 (0%) 0 (0%) Follow-up renogram after 6 months Patent 18 (100.0%) 19 (100.0%) – Obstructed 0.0% 0 (0%) SD, standard deviation; PO: postoperative; US: ultrasound.